The prevalence of elder abuse in the Porto Alegre metropolitan area - Camila Mello dos Santos; Renato Jose De Marchi; Aline Blaya Martins; Fernando Neves Hugo; Dalva Maria Pereira Padilha; Juliana Balbinot Hilgert (Sociedade Brasileira de Pesquisa Odontológica, 2013)
Abuse of the elderly is a form of violence to come to the public's attention. Dental professionals are in an ideal position to identify physical abuse. The aim of this study was to assess the prevalence of elderly abuse and analyze the database of injury reports that can be identified by dental teams. A documentary analysis study developed by the Elderly Protection Police Station of Porto Alegre, Rio Grande do Sul, was carried out. The information used came from 2,304 complaints filed at the aforementioned institution between the years of 2004 and 2006. The records of abuse are categorized as injury, neglect, mistreatment, theft, financial abuse, threat, disturbing the peace, atypical fact, and others. The injuries that could be identified by the dental team were classified according to the injury's location in the area of the head, face, mouth and neck. Descriptive analysis was performed, and chi-square tests were used to evaluate the distributions of the types of elder abuse in relation to sex and age. The most frequent of the different types of abuse was theft, with a prevalence of 17.8%, followed by disturbing the peace at 11.8%. Disturbing the peace, threat, and bodily injury were significantly associated with women. Elder abuse among women and men declines with age. The prevalence of head injury was 25% of the total injuries, most often in females, and in those aged < 70 years. Based on these results, it is necessary that the dental team observe the elderly person's appearance for suspicious physical signs.